2008
DOI: 10.1590/s0004-282x2008000400026
|View full text |Cite
|
Sign up to set email alerts
|

Thrombosed developmental venous anomaly Associated with cerebral venous infarct

Abstract: Developmental venous anomaly (DVA), also known as venous angioma, is becoming the most commonly encountered intracranial vascular malformation in central nervous system (CNS) CaSEA 19 years old woman presented with acute onset of syncope, followed by left side of the body weakness and numbness. MRI revealed a dilated vascular structure at right frontal lobe, filled with hyperintense material on unenhanced T1-weighted sequences. It was thought to represent a thrombosed venous collector of a DVA, draining tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Hemorrhagic or ischemic infarction around a DVA may result from acute thrombosis of the collecting vein35–49 (Fig 5), although it may also be observed in rare instances in the presence of a patent venous collector 50, 51. A review of the literature revealed 19 documented cases of symptomatic thrombosed DVAs (Table) presenting with venous ischemic infarction (53%), parenchymal hemorrhage (37%), subarachnoid and intraventricular hemorrhage (5%), and no intraaxial or extraaxial lesions (5%) 35–49. Management was conservative in eight cases (42%), and involved anticoagulation in seven (37%) and decompression surgery for evacuation of a compressive hematoma or mass effect secondary to venous infarction in four (2%).…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Hemorrhagic or ischemic infarction around a DVA may result from acute thrombosis of the collecting vein35–49 (Fig 5), although it may also be observed in rare instances in the presence of a patent venous collector 50, 51. A review of the literature revealed 19 documented cases of symptomatic thrombosed DVAs (Table) presenting with venous ischemic infarction (53%), parenchymal hemorrhage (37%), subarachnoid and intraventricular hemorrhage (5%), and no intraaxial or extraaxial lesions (5%) 35–49. Management was conservative in eight cases (42%), and involved anticoagulation in seven (37%) and decompression surgery for evacuation of a compressive hematoma or mass effect secondary to venous infarction in four (2%).…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Drainage vein thrombosis of a DVA is rare, and only 28 patients with 29 cases of symptomatic thrombosed DVAs have been reported in the literature [1,2,3,4,5,6,7,8,9,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28]. These patients had a variety of presentations including venous ischemic infarction (n = 16, 55%), parenchymal hemorrhage (n = 8, 28%), venous congestive edema (n = 3, 10%), or subarachnoid hemorrhage (n = 2, 7%).…”
Section: Discussionmentioning
confidence: 99%
“…Among those 20, three had cerebellar DVAs [14, 18, 19], and one case presented with only with subarachnoid hemorrhage and no infarction [18]. Two cases had ICH only [8, 12] and f ive cases [7, 9, 15, 16] showed findings of ICH and venous infarction on the initial brain images. Most of them presented only CT, MRI or angiographic images at the initial diagnosis or at certain time points.…”
Section: Discussionmentioning
confidence: 99%